Rational development of gemcitabine-based nanoplatform for targeting SERPINB9/Granzyme B axis to overcome chemo-immune-resistance - Haozhe Huang; Yiqing Mu; Yixian Huang; Beihong Ji; Yifei Wang; Chien-Yu Chen; Yuang Chen; Zhangyi Luo; Sihan Li; Ziqian Zhang; Luxuan Wang; James F. Conway; et al. (Nature Communications)
Abstract SERPINB9, an endogenous inhibitor of granzyme B (GzmB), has emerged as a critical factor in the resistance to immunotherapy by protecting cancer cells from GzmB-induced cytotoxicity. However, its role in chemosensitivity remains unknown. In this study, we show that gemcitabine (GEM) treatment upregulates SERPINB9 through transcription factor ATF-3. Interestingly, GEM also induces the expression of GzmB and knockout or knockdown of SERPINB9 results in enhanced response of tumor cells to GEM, suggesting a role of GzmB/SERPINB9 axis in regulating chemosensitivity. To facilitate the therapeutic translation of these findings, we engineer POEM nanocarrier (consisting of lipid-derivatized polylysine (PEG-PLL-Oleic acid, PPO), and GEM-conjugated polylysine (PEG-PLL-OA-GEM, PPOGEM), PPO/PPOGEM (POEM)) that is highly effective in codelivery of built-in GEM and loaded SERPINB9 short interfering RNA (siSPB9). GEM conjugation introduces an additional mechanism of carrier/siRNA interaction in addition to charge-mediated interaction and enables efficient i.v. delivery at lower N/P ratios. Here, we show that co-delivery of GEM and siSPB9 significantly improves antitumor efficacy and remodels the tumor immune microenvironment in pancreatic cancer models, supporting a promising therapeutic strategy.